El origen del códice maya Tro-cortesiano. Un pleito, una condesa y un virrey - Andrés Gutiérrez Usillos (Journal de la Société des Américanistes)
The origin of the Mayan codex known as Tro-cortesiano has been unknown for more than one hundred and fifty years since its appearance in Spain. Several theories have tried to explain the precise place and time in which this codex was elaborated, or the date and circumstances in which it arrived to the Iberian Peninsula. In this article we will review the data that were known in the 19th century about the origin of the codex, to discover what could have been its true origin, its relationship with the Counts of Cancelada and, from there, to complete the knowledge of this exceptional pre-Hispanic document.